SUSTAINABLE EVENT MANAGEMENT : A Practical Guide - Jones, Meegan (Routledge, 2018)
Across the world each year events of every shape and size are held: from community events, school fairs and local business functions through to the world’s largest festivals, music events, conferences and sporting events. As well as causing celebration and giving voice to issues, these public parties use up resources, send out emissions and generate mountains of waste. Events also have the power to show sustainability in action and every sustainably produced event can inspire and motivate others to action. Written by a leader in event sustainability management, this book is a practical, step-by-step guide taking readers through the key aspects of how to identify, evaluate and manage event sustainability issues and impacts and to use the event for good – it's for events of any style and scale, anywhere in the world